Molecular dynamics simulation of diffusionless phase transformation in a quenched NiAl alloy model - Ozgen, S; Adiguzel, O (Pergamon-Elsevier Science Ltd, 2003)
Interatomic potentials have great importance in the analysis and calculations of some parameters in atomic scale. These calculations are realised by the computer simulation techniques. In the present study, a molecular dynamics (MD) simulation method which allows the system to vary in shape and size was used for the investigation of diffusionless phase transformation in Ni-37.5 at.%Al alloy model which exhibits shape memory effect in this composition. Interatomic forces were determined by the gradient of Lennard-Jones potential function, and the potential parameters were optimised by the MD simulations. Optimisation was done corresponding to the crystal lattice properties and melting point. The crystallographic properties of the alloy were investigated in high temperature phase (B2-type super-lattice) field, and diffusionless phase transformation was carried out by means of a rapid cooling method. Also, lattice faults were observed in the crystal structure after the transformation. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: interatomic potentials; computer simulation; shape memory alloys